Atomic force microscopy of single- and double-stranded DNA. - Hansma, H G (1992)
A method has been developed for imaging single-stranded DNA with the atomic force microscope (AFM). phi X174 single-stranded DNA in formaldehyde on mica can be imaged in the AFM under propanol or butanol or in air. Measured lengths of most molecules are on the order of 1 mu, although occasionally more extended molecules with lengths of 1.7 to 1.9 mu are seen. Single-stranded DNA in the AFM generally appears lumpier than double-stranded DNA, even when extended. Images of double-stranded lambda DNA in the AFM show more sharp kinks and bends than are typically observed in the electron microscope. Dense, aggregated fields of double-stranded plasmids can be converted by gentle rinsing with hot water to well spread fields.